2015
DOI: 10.1037/adb0000075
|View full text |Cite
|
Sign up to set email alerts
|

Premeditation moderates the relation between sensation seeking and risky substance use among young adults.

Abstract: Young adulthood is a peak period for externalizing behaviors such as substance abuse and antisocial conduct. Evidence from developmental neuroscience suggests that externalizing conduct within this time period may be associated with a “developmental asymmetry” characterized by an early peak in sensation seeking combined with a relatively immature impulse control system. Trait measures of impulsivity—sensation seeking and premeditation—are psychological manifestations of these respective systems, and multiple p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 100 publications
(175 reference statements)
2
24
2
Order By: Relevance
“…McCabe et al found that premeditation enhanced the associations between sensation seeking and multiple substance use behaviors but this interaction did not extend to predict antisocial behaviors. Our current findings were slightly different than those of McCabe et al (2015) in that the premeditation by negative urgency interaction was only significant for sexual partners in the past 5 years, but not for past-year unprotected sex while under the influence, which is conceptually more related to substance use. Clinically high-risk samples are particularly prone to experiencing poor emotional self-regulation (Gratz & Tull, 2010; Leadbeater, Blatt, & Quinlan, 1995), and the experience of frequent or acute negative affect increases chances of engaging in avoidant coping mechanisms (Westen, 1994), which have been linked to engagement in risky sex behaviors (Folkman, Chesney, Pollack, & Phillips, 1992).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…McCabe et al found that premeditation enhanced the associations between sensation seeking and multiple substance use behaviors but this interaction did not extend to predict antisocial behaviors. Our current findings were slightly different than those of McCabe et al (2015) in that the premeditation by negative urgency interaction was only significant for sexual partners in the past 5 years, but not for past-year unprotected sex while under the influence, which is conceptually more related to substance use. Clinically high-risk samples are particularly prone to experiencing poor emotional self-regulation (Gratz & Tull, 2010; Leadbeater, Blatt, & Quinlan, 1995), and the experience of frequent or acute negative affect increases chances of engaging in avoidant coping mechanisms (Westen, 1994), which have been linked to engagement in risky sex behaviors (Folkman, Chesney, Pollack, & Phillips, 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the current findings supported the utility of the UPPS-P impulsivity measure as a clinical or screening tool to identify individuals who might be at elevated risk for risky sex behaviors. Moreover, this study supported the developmental asymmetry theory proposed by McCabe et al (2015), further expanding the research to include risky sex behaviors. These findings underscored the importance of personality factors as they relate to risky sex behaviors and the importance of incorporating such factors into prevention and intervention programs specifically tailored for young adults with a history of externalizing psychopathology.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations